Understanding climate literacy research using scientometrics analysis - Rahmawaty; Ismail, Mohd Hasmadi; Rauf, Abdul; Abdullah, Muhammad Fuad; Mohd Noor, Mohd Iqbal; Amir Mustafa, Amira Mas Ayu; Gandaseca, Seca; Karuniasa, Mahawan; Yekyoum, Kim; Suratman, Mohd Nazip; Salleh, Siti Aekbal; Tedong, Peter Aning (Elsevier, 2024)
Climate literacy, critical for understanding both the individual’s impact on climate and the consequential effects on society and the biosphere, is comprehensively examined in this study through scientometric analysis. Spanning research from 1981 to 2024 and utilizing the Web of Science database, this study maps the evolution of publication trends, pinpoints central themes, and identifies pivotal publications within the domain. Leveraging advanced visualization tools like CiteSpace, the research employs dual-map overlays and document co-citation analysis to uncover the intricate web of interconnections among scholarly works. Findings highlight a significant surge in publications after 2015, mirroring the escalating global consciousness of climaterelated issues. Predominant research clusters identified include “bad news,” “mental health,” and "farmers’ perceptions,” showcasing the field’s thematic diversity. These insights emphasize the indispensable role of interdisciplinary methods in advancing public knowledge and active participation in climate change mitigation and adaptation efforts, fostering a well-informed community poised to address environmental challenges.